2017
DOI: 10.1136/heartjnl-2016-310828
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in adults with congenital heart disease and associations with functional outcomes

Abstract: Categorisation of patientswith CHD with the IPAQ quickly provides clinical information as HEPA patients have a less probability for impaired HrQoL and diminished exercise capacity. Nevertheless, the IPAQ cannot substitute an accelerometer-based assessment for PA, nor a CPET for exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
3
26
1
2
Order By: Relevance
“…We found that the complexity of CHD was associated with physical activity level. This finding contrasts with previous reports [ 12 , 42 , 44 ]. In two previous studies, a slightly different definition of complexity was applied with two groups of complexity instead of three as used in this present investigation [ 35 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the complexity of CHD was associated with physical activity level. This finding contrasts with previous reports [ 12 , 42 , 44 ]. In two previous studies, a slightly different definition of complexity was applied with two groups of complexity instead of three as used in this present investigation [ 35 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Being unable to be physically active like others seemed to create a feeling of exclusion with a negative impact on their social life. This is also confirmed in studies where low physical activity level and inactivity is related to impaired mental and physical health‐related quality of life (Muller et al., ). Their wish to be like others is in agreement with earlier research where the struggle for normality is described as an ongoing dynamic process, which varies throughout the lifespan (Claessens et al., ; Overgaard et al., ).…”
Section: Discussionsupporting
confidence: 52%
“…1 Due to progress made in the fields of early diagnostics, surgical techniques, and follow-up, the percentage of patients reaching adulthood has constantly risen over the last few decades and is now over 90%. [2][3][4] With higher life expectancy, new aims develop that go far beyond reaching adulthood and move focus on lifestyle and quality of life. One key aspect contributing to the improvement of quality of life in these patients is their physical well-being and fitness.…”
mentioning
confidence: 99%